ANALISIS WAKTU SIKLUS LAMPU LALU LINTAS DENGAN PEMODELAN BERBASIS AGEN - YASTICA, TIARA VERITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Annually the amount of vehicle in Yogyakarta Special Region has been increasing. It is clearly seen from the traffic which is full of two-wheeler. Traffic jam becomes one of the problems that people of Yogyakarta has to face each day, due to the increasing number of the vehicle which is not followed by the addition of road's total length. One of the solutions to decrease the jam is to manage the traffic with the help of traffic lights. In reality, the function of traffic light is to create the road's condition to be safe and swift. But, if the duration of each lamp isn't regulated in order, the presence of traffic lights will be the source of the jam itself. Based on the situation above, a study about determining the timing of each lamp in cycle is conducted, so that the traffic jam due to unregulated lamp timing cycle will be decreased. The study is conducted at Condong Catur intersection, Yogyakarta Special Region. The method which is used in this study is a simulation based on agents when the driver and how they drive become one of the aspects used to determine the time cycle of the traffic lights, mainly from how the driver control the speed of their ride based on the traffic lights and all the surrounding vehicles. The driver will be modeled as an unique individual and is able to make decision either by themselves or by an interaction with others. The data that is used in this study is the data regarding the arrival of vehicles for each track and the average speed of each vehicle. The result that is obtained from the simulation is the average of waiting time from each vehicle for one track. The data will be used later as one of the assessment factor in determining the duration of the traffic light. To get a better systematization of the traffic light, the researcher used the 24 experiment design. The simulation result for the light's timing regulation is appropriate with the real system, with the waiting time average of 79 seconds for each vehicle, and with the north, east, south, and west's waiting time start from 109 seconds, 71 seconds, 69 seconds, and 67 seconds. The amelioration scenario with the lowest waiting time is produced by the systematization of the green's and yellow light's duration